Efficacy and safety of duloxetine in osteoarthritis: a systematic review and meta-analysis - Osani, Mikala C. (Korean J Intern Med, 2019)
About 21% of adults with osteoarthritis (OA) are diagnosed with concomitant depression in addition to chronic pain. Duloxetine, an anti-depressant medication, has been recently approved for managing Knee OA. We performed a systematic review to ascertain the efficacy and safety of duloxetine for OA. We searched MEDLINE, EMBASE, Web of Science, Google Scholar, and the Cochrane Database from inception to December 2018. Randomized clinical trials (RCTs) assessing the efficacy and/or safety of duloxetine versus placebo in OA patients were included. Data extraction and quality assessment were undertaken by two independent reviewers. Seven RCTs (n = 2,102 participants) met our inclusion criteria, and five RCTs (n = 1,713) were eligible for meta-analysis. The results of our analyses indicate that duloxetine has statistically significant, moderate benefits on pain, function, and quality of life in knee OA patients for up to 13 weeks. Reported incidences of gastrointestinal adverse events were three to four times higher in participants who received duloxetine versus placebo. Duloxetine may be an effective treatment option for individuals with knee OA, but use of the drug is associated with a significantly higher risk of adverse events. Patient preferences and clinicians’ judgment must be considered before the initiation of duloxetine.